Analisis Pengaruh Media Pendingin Dengan Kombinasi Waktu Penahanan Pendingin Terhadap Nilai Kekerasan Baja AISI-1045 Pada Proses Quenching - Somawardi; Sugianto; ERVAN AGUSTIAN (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
AISI-1045 steel has a hardness of 7,167 HRC without treatment. The hardness of this steel can be increased through the hardening process with rapid cooling. This study aims to determine the optimum hardness value and how the effect of cooling media (brine, water, and oil) with a combination of coolant holding time (5, 10, and 15 minutes) which received quenching heat treatment against the hardness of AISI-1045 carbon steel. The heating process is carried out at a temperature of 900º C using an electric oven. This study used AISI-1045 steel with a diameter of 25 mm and a length of 25 mm. Tests carried out using a Universal Hardness Tester (Rockwell). The hardness is influenced by the type of cooling medium and the holding time of the coolant. Based on the fast cooling carried out from the three media with variations in the cooling holding time, it produces varying levels of hardness. From the heat treatment that has been done, the highest hardness value is in the brine medium with a coolant holding time of 15 minutes (G15) with an average value of 53,283 HRC. And the lowest hardness value is the oil medium with a coolant holding time of 5 minutes (O5) with an average value of 21,583 HRC.